Pemanfaatan Minuman Herbal Berbasis Daun Kelor sebagai Terapi Komplementer Pencegahan Anemia pada Remaja Putri di SMA - Tri Sartika; Ayu Devita Citra Dewi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Anemia is a common health problem among adolescent girls, especially in developing countries like Indonesia. This condition is generally caused by insufficient iron intake, an unbalanced diet, and increased iron requirements during growth. Anemia not only impacts physical health but also affects concentration, productivity, and quality of life. Therefore, interventions based on nutrition education and the utilization of local food sources are crucial in sustainable anemia prevention efforts. One potential complementary therapy alternative is the consumption of herbal drinks based on moringa leaves (Moringa oleifera). Moringa leaves are known to be rich in iron, vitamin A, and antioxidants that play a role in red blood cell formation. This community service activity aims to increase the knowledge and skills of adolescent girls in utilizing moringa leaves as a natural source of iron. The target group is grade 10 and 11 female students at SMA Sejahtera Palembang, which was held in June 2025. The activity methods included a nutrition lecture on anemia and the importance of iron, an interactive discussion on the benefits of moringa leaves, and hands-on practice in making herbal moringa drinks (such as moringa leaf tea and moringa juice). The material was delivered using a communicative and participatory approach to actively engage participants. The results of the activity showed an increase in participants' understanding of the causes of anemia, the benefits of moringa leaves, and their willingness to consume herbal drinks as a preventative measure. Most participants also expressed interest in trying to make their own moringa herbal drink at home. This activity is expected to become part of school-based promotional and preventive efforts to address anemia in adolescent girls.